2009
DOI: 10.1177/0748730409349895
|View full text |Cite
|
Sign up to set email alerts
|

Correlation with Behavioral Activity and Rest Implies Circadian Regulation by SCN Neuronal Activity Levels

Abstract: The SCN of the hypothalamus contains a major pacemaker, which exhibits 24-h rhythms in electrical impulse frequency. Although it is known that SCN electrical activity is high during the day and low during the night, the precise relationship between electrical activity and behavioral rhythms is almost entirely unknown. The authors performed long-term recordings of SCN multiple unit activity with the aid of implanted microelectrodes in parallel with the drinking activity in freely moving mice. The animals were k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 51 publications
3
51
1
Order By: Relevance
“…Methylphenidate treatment also altered SCN electrical activity, producing a delayed trough, increased amplitude, and reduced variability. Changes in the SCN MUA rhythm, specifically the downward slope and trough, have been previously shown to correlate with behavioral activity (Houben et al, 2009), a pattern observed in the present study. All parameters of the SCN waveform taken together (trough, peak, rising, and downward slope) were also shifted, suggesting a delay in the SCN electrical activity rhythm.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Methylphenidate treatment also altered SCN electrical activity, producing a delayed trough, increased amplitude, and reduced variability. Changes in the SCN MUA rhythm, specifically the downward slope and trough, have been previously shown to correlate with behavioral activity (Houben et al, 2009), a pattern observed in the present study. All parameters of the SCN waveform taken together (trough, peak, rising, and downward slope) were also shifted, suggesting a delay in the SCN electrical activity rhythm.…”
Section: Discussionsupporting
confidence: 70%
“…Animals in the behavioral part of the study were individually housed in cages equipped with running wheels (n ¼ 24), with passive infrared motion sensors (PIRs, n ¼ 12), or with both (n ¼ 9). Animals in the electrophysiology and sleep part of the study were individually housed in standard mouse cages before recording, and were transferred to large recording chambers (Deboer et al, 2007b;Houben et al, 2009). Animals started the experiment under a 12 h : 12 h lightdark cycle, with ad libitum access to food and drink throughout the experiment.…”
Section: Animals and Housingmentioning
confidence: 99%
See 1 more Smart Citation
“…P hysiology and behavior of all mammals is organized in an alternating pattern of rest and activity cycles, whereby the endogenous and light-induced daily neuronal activity of the suprachiasmatic nucleus (SCN) signals rest in nocturnal rodents and activity in diurnal primates, such as humans (1,2). Restricting food access to a short and predictable episode during the rest phase changes this behavioral pattern, such that an animal becomes active and for up to several hours anticipates the upcoming feeding event.…”
mentioning
confidence: 99%
“…Recent experimental results demonstrate that circadian modulation of behavioural activity is reliably predicted by the circadian variation of SCN electrical activity [1]. In both nocturnal and diurnal animals, the overall firing rate of SCN neurons varies over 24 h, with a generally higher firing rate during the light period and a generally lower firing rate during the dark period [2][3][4], though some subpopulations show different firing profiles [5][6][7].…”
Section: Introductionmentioning
confidence: 99%